1990
DOI: 10.1063/1.102719
|View full text |Cite
|
Sign up to set email alerts
|

Kinetics of silicon epitaxy using SiH4 in a rapid thermal chemical vapor deposition reactor

Abstract: The equilibrium hydrogen surface coverage on Si(100) during silicon epitaxy using SiH4 has been measured in a rapid thermal chemical vapor deposition reactor. The hydrogen coverage could be ‘‘frozen out’’ completely on the surface by a rapid cool-down and pump-down of the reactor up to temperatures of ≂575 °C; at temperatures above 575 °C only partial ‘‘freeze-out’’ is achieved. Surface hydrogen was titrated in situ using the reactor as a thermal desorption spectrometer. Epitaxial silicon films were grown in t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
49
0

Year Published

1991
1991
2020
2020

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 138 publications
(55 citation statements)
references
References 9 publications
6
49
0
Order By: Relevance
“…It is apparent that the growth of both types of films is surface reaction limited. However, the detailed rate limiting reactions may be different: The apparent activation energy for the epitaxy is calculated to 2.1 eV, in agreement with reported results, 11,12 whereas the growth of polycrystalline Si shows an apparent activation energy of 1.6 eV, which is consistent with the literature. 5,13,14 It was previously reported that the apparent activation energies were closely related to the hydrogen surface coverage.…”
Section: A Film Growthsupporting
confidence: 85%
“…It is apparent that the growth of both types of films is surface reaction limited. However, the detailed rate limiting reactions may be different: The apparent activation energy for the epitaxy is calculated to 2.1 eV, in agreement with reported results, 11,12 whereas the growth of polycrystalline Si shows an apparent activation energy of 1.6 eV, which is consistent with the literature. 5,13,14 It was previously reported that the apparent activation energies were closely related to the hydrogen surface coverage.…”
Section: A Film Growthsupporting
confidence: 85%
“…The activation energy of the SiH 4 reaction rate constant shown in the figure caption is 2 eV, which is in good agreement with that of the deposition rate for higher P SiH4 , and also with that in other investigations. 25) It has been reported that the Si deposition is limited by SiH decomposition, in other words, hydrogen desorption from SiH. 25,26) It is found that the SiH 4 reaction rate constant, k Si on Si n 0 , agrees with the SiH constant estimated from ref.…”
Section: Si and Ge Epitaxial Growthsupporting
confidence: 77%
“…25) It has been reported that the Si deposition is limited by SiH decomposition, in other words, hydrogen desorption from SiH. 25,26) It is found that the SiH 4 reaction rate constant, k Si on Si n 0 , agrees with the SiH constant estimated from ref. 27 within 50%.…”
Section: Si and Ge Epitaxial Growthsupporting
confidence: 77%
“…For comparison, the doping properties using SiH 4 were also evaluated. The growth temperature was set at 650 8C as a typical condition for the silicon epitaxial growth with SiH 4 [18]. The dependence of the phosphorus concentration on PH 3 flow, as observed in phosphorus-doped silicon layers grown with Si 2 H 6 or SiH 4 , is shown in Fig.…”
Section: Resultsmentioning
confidence: 99%